Hubungan kemampuan mengelola emosi dengan kecenderungan berperilaku agresif siswa - Mutiara Eka Putri; Herman Nirwana; Indah Sukmawati (IICET (Indonesian Institute for Counseling, Education and Therapy), 2020)
This research is motivated by the number of students who have a tendency to behave aggressively. One of the factors that is thought to influence is the ability to manage emotions. The purpose of this study is to describe (1) the tendency to behave aggressively, (2) the ability to manage emotions, and (3) test the relationship between the ability to manage emotions and the tendency to behave aggressively in students. The population of the study was 205 students of SMP N 1 X Koto Singkarak in the July-December semester of the 2018/2019 academic year and a sample of 138 students was selected by Stratified Random Sampling. The instrument used is the Aggressive Behavior Trending questionnaire with a reliability of 0.942 and the Emotion Management Ability questionnaire with a reliability of 0.741. Data were analyzed by descriptive techniques and Pearson Product Moment. The research findings are: (1) the tendency of aggressive behavior of students in the high category, (2) the ability to manage students' emotions in the very low category, and (3) there is a significant negative relationship between the ability to manage emotions and the tendency to behave aggressively in students.